Book review: Anil K. Khandelwal, CEO: Chess Master or Gardener? How Game-changing HR Reforms Created a New Future of Bank of Baroda. Issue 1 (March 2018) - Panda, Abinash
Anil K. Khandelwal, CEO: Chess Master or Gardener? How Game-changing HR Reforms Created a New Future of Bank of Baroda, 2018, New Delhi: Oxford University Press, 358 + xxvi pp., ₹750. ISBN: 978-0-19-948564-2.